In vitro morphogenesis of Cattleya intermedia Graham ex Hook (Orchidaceae) seedlings in different concentrations of basal culture medium (Research, Society and Development, 2023)
Cattleya intermedia Graham ex Hook is a native Brazilian orchid from the south of the Atlantic Forest with economic interest as an ornamental plant. Plant tissue culture makes it possible to produce orchids on a large scale, with a view to marketing and conserving the species. The aim of this study was to evaluate the effect of different concentrations of MS basal culture medium on the initial in vitro growth of the aerial and root parts of C. intermedia seedlings, with a view to propagating them as a strategy for use in plant biofactories. Seedlings in vitro germinated were subjected to growth and development in Murashige & Skoog culture medium at different salt concentrations (100%, 50% and 25%). The experiment was organized in a completely randomized design, with ten replicates for each treatment, followed by analysis of variance and the SNK test. The use of MS basal culture medium at full concentration in C. intermedia cultivation favors greater seedling survival and a higher percentage and number of regenerated shoots. For the adventitious rooting of seedlings in vitro cultivation, the use of basal culture medium diluted to 25% favors the percentage of rooting and the average length of the roots.